PATTERN SEASON CATCH FISH DISEASE (Euthynus Affinis) BASED ON LANDING DATA IN SIBOLGA SUMATERA UTARA - Doni Simanjuntaki; Usman Usman; T. Ersti Yulika Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on November 2017 at Nusantara Port of Sibolga, North Sumatera Province. The purpose of this study is to study the timing of the catching season to catch tuna (Euthynnus Affinis) and to obtain fluctuation of catch fish in Sibolga waters. This study uses survey method, monthly production data and data effort obtained from VAT Sibolga, North Sumatra Province and analyzed with the average percentage based on time series. Based on the calculation of the average percentage method so as to get the Season of the Catching Index (IMP) for five years, fish Tongkol in Sibolga waters can be caught throughout the year. The catching season is in March, April, May and November with the peak of the arresting season in November that is in the West season. Key word : The pattern of tuna fishing season